2020
DOI: 10.1186/s12868-020-00567-3
|View full text |Cite
|
Sign up to set email alerts
|

Noise exposure alters MMP9 and brevican expression in the rat primary auditory cortex

Abstract: Background: This study aimed to investigate the changes in molecules related to perineuronal nets (PNNs) and synaptic transporters in the primary auditory cortices of rats with noise-induced hearing loss. Female Sprague-Dawley rats at postnatal day 7 were divided into the noise and control groups. Four hours of 115 dB SPL white noise was delivered for 10 days to the noise group. Thirty days after noise exposure, the primary auditory cortex and the inferior colliculus were harvested. The expression levels of ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Six to eight hours after the ABR measurement, all rats were sacrificed and their hippocampi (n = 15 per group) and primary temporal cortices (n = 6 per group) were harvested. The euthanasia was conducted by carbon dioxide inhalation with flow rate of 5–6 L/min in 25.40 ×48.26 ×22.86 cm size cage, as previously described [ 17 ]. The dorsal cornu ammonis 3 (CA3) region of the rat hippocampus was located in a reference atlas, and identical tissue samples were dissected from adjacent regions of CA2 and the dentate gyrus [ 18 ]).…”
Section: Methodsmentioning
confidence: 99%
“…Six to eight hours after the ABR measurement, all rats were sacrificed and their hippocampi (n = 15 per group) and primary temporal cortices (n = 6 per group) were harvested. The euthanasia was conducted by carbon dioxide inhalation with flow rate of 5–6 L/min in 25.40 ×48.26 ×22.86 cm size cage, as previously described [ 17 ]. The dorsal cornu ammonis 3 (CA3) region of the rat hippocampus was located in a reference atlas, and identical tissue samples were dissected from adjacent regions of CA2 and the dentate gyrus [ 18 ]).…”
Section: Methodsmentioning
confidence: 99%
“…The chondroitin sulfate proteoglycans (CSPGs), such as brevicans and neurocans, are composed of PNs [ 4 ]. Changes in the PNs following noise exposure have been reported in the primary auditory cortex [ 5 , 6 ]. However, the changes in PNs or CSPGs have not been explored in the auditory brainstem of noise-induced hearing loss model.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated the changes of CSPGs including brevican in auditory nervous system following noise-induced hearing loss [ 5 , 6 ]. The mediating role of miRNAs were suggested for the changes of CSPGs in visual cortex [ 14 ].…”
Section: Introductionmentioning
confidence: 99%